1993
DOI: 10.1063/1.860575
|View full text |Cite
|
Sign up to set email alerts
|

Integral eigenmode analysis of shear flow effects on the ion temperature gradient mode

Abstract: Previous numerical and analytic kinetic studies 1-3 have investigated the influence of velocity shear on the ion temperature gradient (ITG) mode. These studies relied on a differential approximation to study mode structures with kj.p_ << 1. A recently developed gyrokinetic integral code is here used to explore the effects of sheared flows on the ITG mode for arbitrary values of k.pi. It is found that both the mode structure and eigenfrequencies predicted by the integral code can differ from the results obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This situation differs somewhat from the case with finite magnetic shearŝ 10,37 , where there are linearly growing modes for a finite range of γ E . At finite magnetic shear, growing eigenmodes are possible because while γ E leads to an effective dependence of the radial wavenumbers on time,ŝ makes them dependent also on the position along the field line.…”
Section: Subcritical Turbulencementioning
confidence: 73%
“…This situation differs somewhat from the case with finite magnetic shearŝ 10,37 , where there are linearly growing modes for a finite range of γ E . At finite magnetic shear, growing eigenmodes are possible because while γ E leads to an effective dependence of the radial wavenumbers on time,ŝ makes them dependent also on the position along the field line.…”
Section: Subcritical Turbulencementioning
confidence: 73%
“…finite maximum and then decreases towards zero, which it reaches at t = t 0 , whereupon growth turns to decay. 5 Thus, there is a period of strong transient amplification, which lasts for a finite fraction of time t 0 . The amplification exponent is…”
Section: Case Of Weak Shearmentioning
confidence: 99%
“…Stimulated by the experimental observations, the ion temperature gradient ͑ITG͒ driven instability has been studied intensively and significant progress has been made in the last decade. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Currently, it is widely accepted that linear and nonlinear ITG instability theories and simulations are enough to explain the ion transport anomaly qualitatively. It has been shown that the ion thermal diffusivity reduces to the neoclassical level in advanced tokamak plasmas with internal transport barriers ͑ITB's͒.…”
Section: Introductionmentioning
confidence: 99%